2011
DOI: 10.1109/tmag.2010.2092420
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Ferrite Film Inductor for Power System-on-Chip (PowerSoC) Smart Phone Applications

Abstract: An array of ferrite and air-core inductors was fabricated on silicon wafer to characterize inductor performance. The 1 m and 2.5 m thick ferrite films for the fabrication of inductors were prepared by dc magnetron sputtering. The inductance of the ferrite inductor increased with the thickness of ferrite film from 45.5 nH for 1 m thick ferrite to 50 nH for 2.5 m thick ferrite. The maximum Q-factor was obtained to be 59 at 2.87 MHz from 2.5 m thick ferrite inductor, which is higher than 49.3 at 2.26 MHz for 1 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A lot of research has been carried out to achieve inductor integration on-chip or in-package. Some demonstrators of air-core inductors, such as thin film magnetic inductors and ferrite based ones, have shown that each integration method has its own merits and difficulties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. For on-chip integration, approaches to the fabrication of micro-inductors involving vacuum deposition and electrodeposition of magnetic cores have been demonstrated over the last thirty years.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has been carried out to achieve inductor integration on-chip or in-package. Some demonstrators of air-core inductors, such as thin film magnetic inductors and ferrite based ones, have shown that each integration method has its own merits and difficulties [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. For on-chip integration, approaches to the fabrication of micro-inductors involving vacuum deposition and electrodeposition of magnetic cores have been demonstrated over the last thirty years.…”
Section: Introductionmentioning
confidence: 99%